A inclusão escolar nos discursos veiculados pela educação especial: estratégia discursiva de subjetivação docente - Mohr, Alana Claudia (2014)
This study has as focus on the discourses demonstrated by integration/inclusion that actually, it has been defining and redefining the education concerning to the perspective of the school s inclusion and ways of being a teacher. Therefore, it appeared the necessity to understand how teachers are being narrated and developed from the speeches concerning to the School s Inclusion. The research got in a post-structuralist approach, combined with Foucault's theories. It brings the notion of the speeches as a methodological concept and it takes the governamentality to operate as the main analytic s tool. It was possible to noticed the discourses around the School s Inclusion has been used by reason of the State, which makes this process imperative leading the professor s actions, showing to the teachers from the production of certain discursive strategies. Thus, with the analysis of the materials, it was possible to identify the recurrence of three subjectivity strategies discourse, being the operationalization around this, firstly, the felling, the acceptance and professor s consciousness concerning to the introduction of the students with disabilities in regular student s classes. After this, it was identified the strategy discourse around the teacher s responsibility for the success and promotion of the School s Inclusion of these students. And finally, with the movement from this acceptance and responsibility, it was found the third discursive strategy working around the capacity discourses and frequently training for the professors as an indispensable condition to them getting to promote the inclusion and be considered a competent teacher. From the analysis, can be thought, for example, that these discursive strategies of teacher subjectivity are placed consciousness into the operation in order to lead and govern the conduct of the teachers, creating ways of being in contemporary teaching, among others, can identify the teacher while enterprising of himself, who constantly invest in itself, to attend the order of the School s Inclusion.